Automation Of the Fruit Drying Process - Olimov Bobir; Sattarov Asadbek (Genius Journals, 2023)
This dissertation focuses on the automation of the fruit drying process, aiming to enhance efficiency, improve product quality, and reduce labor costs in the fruit processing industry. The study investigates the implementation of automated systems and technologies in the various stages of the fruit drying process, including fruit selection, preparation, drying, and packaging. The research also examines the impact of automation on product characteristics such as color, texture, and nutritional content. The findings indicate that automation offers significant advantages in terms of increased productivity, reduced manual labor, consistent quality, and improved overall efficiency. The dissertation concludes with recommendations for future research and the practical implications of automating the fruit drying process
Keywords: automation; fruit drying process; efficiency